Researching the effects of methylprednisoione (mp) and dimethyl sulphoxide (dmso) on the prevention of peritoneal adhesions in rabbits - Fahrettin Alkan; Yılmaz Koç; İlhami Çelik; Muharrem Erol; M.Faruk Aydın (Eurasian Journal of Veterinary Sciences)
The purpose of the study was to evaluate the effect of methylprednisoione (MP) and dimethyl sulphoxide (DMSO) on the prevention of peritoneal adhesions in rabbits. Thirtysix rabbits were used. The rabbits divided into three groups, each having 12 rabbits. In all rabbits in three groups, midline laparotomies were applied. Six- eight longitudinal incision were made on the left peritoneal surface. Area that 1x2cm, was excised from, the right peritoneal surface. Group 1, 2, and, 3 were intraperitoneal^ administered 5 ml/kg of the physiologycal saline (0.9%NaCI solution), 15 mg/kg methylprednisoione in 5 ml of the physiologycal saline, and 1 g/kg dimethyl sulphoxide in 5 ml of the physiologycal saline respectively following the laparotomy, and injections were continued for 5 days after laparotomy. Fourteen days after surgery, all rabbits underwent via a paramedian incision in order to evaluate whether the presence and extend of the adhesions. In the defective areas were taked the biopsy samples from the hystologic researchs. The results suggest that the MP and DMSO used in this study significantly decrease the incidence and degree of peritoneal adhesions when compared to the saline group.